The economic integration of Spain with the E.E.C: Problems and prospects - Juergen B. Donges (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1973)
In 1959/60, there was a radical shift in Spain's economic development strategy from a strongly autarchic to a cautiously outward orientation. A group of neo-liberal technocrats who enterered for the first time since Civil War the governmental administration obviously understood that the establishment of the European Common Market (1957) and the introduction of external convertibility by the highly industrialized countries (1958) would accentuate the economic growth path in Western Europe and, thereby, open new possibilities of rapid economic development for Spain. After all, the Government recognized that economic integration is an important device for promoting economic development. This is particularly true if industrialization is considered as a corner-stone of rapid economic and social progress (as was, and is, the case in Spain). The arguments in favour of more integration are too well known to need a detailed elaboration here. Essentially, they refer to the economies of scale that can be achieved in a wider market than the relatively small national one, to the increase of overall efficiency that will result from the more competitive environment, and to the improvement in the allocation of resources that can take place by arriving at a product-mix according to the country's comparative advantage. Whatever the degree to which Spain was able to reap the benefits of integration, the economic boom, which the country has been experiencing since 1960, and which deserves to be regarded as an outstanding success story in terms of income expansion as well as of growth and structural changes of production and foreign trade proves that the opening of the economy was rewarding thus far.
Keywords: 330